2010
DOI: 10.4065/mcp.2009.0645
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Considerations for Patients With Neuropathic Pain and Other Medical Comorbidities

Abstract: The efficacy of drugs for neuropathic pain has been established in randomized controlled trials that have excluded patients with comorbid conditions and those taking complex medications. However, patients with neuropathic pain frequently present with complex histories, making direct application of this evidence problematic. Treatment of neuropathic pain needs to be individualized according to the cause of the pain, concomitant diseases, medications, and other individual factors. Tricyclic antidepressants (TCAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 56 publications
(43 reference statements)
1
50
0
5
Order By: Relevance
“…Thirdline agents, FDA-approved for the treatment of neuropathic pain, include anticonvulsants such as carbamazepine, lamotrigine, topiramate, phenytoin, and valproic acid and in addition have been observed to have beneficial effect for the modification of emotional lability and irritability during clinical work with Veterans with both PTSD and chronic neuropathic pain. Additional third-line agents include antidepressants such as bupropion, citalopram, and paroxetine, along with topical agents such as capsaicinoid that inhibits the pain-eliciting substance P [86][87][88]. A thorough review of the patient's current medication profile, medical conditions, and potential adverse drug-related effects must be carefully considered and monitored before prescription of any of the above agents.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Thirdline agents, FDA-approved for the treatment of neuropathic pain, include anticonvulsants such as carbamazepine, lamotrigine, topiramate, phenytoin, and valproic acid and in addition have been observed to have beneficial effect for the modification of emotional lability and irritability during clinical work with Veterans with both PTSD and chronic neuropathic pain. Additional third-line agents include antidepressants such as bupropion, citalopram, and paroxetine, along with topical agents such as capsaicinoid that inhibits the pain-eliciting substance P [86][87][88]. A thorough review of the patient's current medication profile, medical conditions, and potential adverse drug-related effects must be carefully considered and monitored before prescription of any of the above agents.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Taking experimental studies as a reference, TNF-α and IL-1β were used to evaluate neuroinflammatory cascade in our study, and a significant increase was observed in the trauma group compared to the control group.It cannot be disregarded that myelinization is an important factor in recovery after nerve damage. In the experimental studies made, it was shown that EPO stimulated myelinization quickly after sciatic nerve damage and provided functional recovery [23]. It was also shown that EPO increased white matter myelin thickness, axon diameter, regenerated and myelinated nerve fibers in central nervous system and spinal cord [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…While statistical tests were conducted, we note that there are large and disparate sample In addition to complaints of pain, patients often present with other multiple coexisting chronic diseases. [5][6][7][8] According to the Centers for Disease Control and Prevention, 47% of U.S. adults aged 55 or greater have 2 or more chronic conditions (e.g., arthritis, asthma, cancer, cardiovascular disease, chronic obstructive pulmonary disease, and diabetes). 9 These diseases require chronic treatment, often with multiple medications.…”
Section: Discussionmentioning
confidence: 99%